Blowing against the Wind? A Narrative Approach to Central Bank Foreign Exchange Intervention - Alain Naef (European Historical Economics Society (EHES), 2020)
Few studies on foreign exchange intervention convincingly address the causal effect of intervention on exchange rates. By using a narrative approach, I address a major issue in the literature: the endogeneity of intraday news which influence the exchange rate alongside central bank operations. Some studies find that interventions work in up to 80% of cases. Yet, by accounting for intraday market moving news, I find that in adverse conditions, the Bank of England managed to influence the exchange rate only in 8% of cases. I use both machine learning and human assessment to confirm the validity of the narrative approach.
Keywords: F31; E5; N14; N24; 330; intervention; foreign exchange; natural language processing; central bank; Bank of England